Development and psychometric properties of a questionnaire to measure drug users' attitudes toward methadone maintenance treatment (DUAMMT) in Iran - Maryam Khazaee-Pool; Zohreh Arefi; Daem Roshani; Tahereh Pashaei; Koen Ponnet (BMC, 2017)
Abstract Background Assessing drug users' attitudes towards different kinds of addiction treatment is necessary to design tailored strategies. The aim of the present study is to develop and examine the psychometric properties of a new scale, called the DUAMMT, for assessing drug users' attitudes toward methadone maintenance treatment in Iran. Methods A multi-phase development method was applied in developing an instrument from February to December 2016. The item generation and scale development were performed through literature review, a qualitative approach, and interviews with an expert panel. Then, the psychometric properties of the scale were evaluated by means of cross-sectional studies with drug users. We performed an exploratory factor analysis, a confirmatory factor analysis, and item-scale correlations; and we tested the internal consistency of the scale. Furthermore, test-retest reliability was evaluated among an Iranian sample of drug users. Results The mean age of participants was 34.12 years. The exploratory factor analysis revealed four factors (perceived barriers, perceived concerns, methadone side effects, and perceived positive effects) containing 17 items that jointly accounted for 60.53% of the observed variance. The confirmatory factor analysis showed a model with appropriate fitness for the data. The Cronbach's alpha coefficient for the subscales ranged from .70 to .79. The intra-class correlation coefficient (ICC) ranged from .774 to .970, which is well above the acceptable threshold. Conclusions The findings of the present study suggest that the DUAMMT is a valid and reliable instrument to measure drug users' attitudes toward methadone maintenance treatment. The DUAMMT can be applied at the start of treatment so that clinical intervention can be targeted to promote retention in treatment.